Enrichment, isolation and biodegradation potential of psychrotolerant polychlorinated-biphenyl degrading bacteria from the Kongsfjorden (Svalbard Islands, High Arctic Norway). Issue 2 (30th January 2017) - Papale, Maria; Giannarelli, Stefania; Francesconi, Sandro; Di Marco, Gaetano; Mikkonen, Anu; Conte, Antonella; Rizzo, Carmen; De Domenico, Emilio; Michaud, Luigi; Giudice, Angelina Lo
Abstract: Persistent organic pollutants (POPs), such as polychlorinated biphenyls (PCBs), have been detected in abiotic Arctic matrices: surface sediments and seawater from coastal areas in the Kongsfjorden were collected and analyzed. Levels of PCBs varied depending on the sampling site. Total PCB concentrations were between 11.63 (site C2W) and 27.69 pg l − 1 (site AW). These levels were comparable to those reported previously in lake sediments from the northern Svalbard. The occurrence and biodegradation potential of cold-adapted PCB-oxidizing bacteria in seawater and sediment along the fjord was also evaluated. After enrichment with biphenyl, 246 isolates were obtained with 45 of them that were able to grow in the presence of the PCB mixture Aroclor 1242, as the sole carbon source. The catabolic gene bph A was harbored by 17 isolates with affiliates to the genera Algoriphagus, Devosia and Salinibacterium that have been never reported as able to utilize PCBs, thus deserving further investigation. The total removal of Aroclor 1242 and selected PCB congeners was evaluated at 4 and 15 °C for eight bph A-harboring isolates and Gelidibacter sp. DS-10. With few exceptions, tested strains showed greater efficiency at 15 than at 4 °C. Isolates were able to reduce most chromatographic peaks by > 50%, with some di- and trichlorobiphenyls that were quite totally removed (> 90%). Highlights: We first report on the degradation ability of PCB-oxidizing Arctic marine bacteria. PCBs were degraded also by bacteria affiliated to genera never reported as able to. The bph A gene confirmed the ability of the isolates to aerobically degrade PCBs. The different congeners in Aroclor 1242 were differently removed at 4 and 15 °C.